PENGEMBANGAN RPS-FLIP BUILDER UNTUK MENINGKATKAN PEMAHAMAN IPA DALAM PEMBELAJARAN DI MASA COVID-19 - Yunianto, Teguh (universitas Ahmad Dahlan, 2021)
The research aims to describe the development of the School Development Plan (RPS-Flip builder) and to find out the validity of the RPS-Flip builder in learning natural science (IPA) during the Covid-19 period. This research method is a development research with the Borg and Gall model. Product trials are carried out on a limited scale by involving students. The results of this study describe the development of the RPS-Flip-builder including the analysis of potential problems, data collection, product design, design validation, product testing, and product revision. Furthermore, the product feasibility results show that the material expert's assessment is 83.25% with the